Karakteristik Tanah untuk Kapasitas Dukung Pondasi Dangkal (Studi Kasus Kabupaten Lembata) - Reyneldis Laurensia Fernandez; Wenceslaus R Fernandez; Frianggi Sofia D Mansari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Determining soil characteristics is a crucial step in foundation planning to ensure adequate soil bearing capacity for structural loads. This study aims to identify soil characteristics in order to determine the appropriate type of foundation, assess potential risks such as soil settlement and failure, and optimize foundation design based on soil data. The methods used include field tests such as cone penetration tests (CPT) and hand boring, as well as laboratory testing of soil samples. Based on cone resistance (qc) results from two soil test points, it was found that qc values are relatively stable at certain depths, with minimum values of 50 kg/cm² and maximum values ≥ 50 kg/cm². These results indicate that the soil at the study site has sufficient bearing capacity for shallow foundations. Furthermore, although the ground surface elevation at the test points varies, the variation does not significantly affect the selection of foundation type. Therefore, shallow foundations are recommended as a suitable system for the soil conditions at this site.